The Leadership Style of Kiai in Sustaining the Institutional Continuity of Nuhuudliyyah Islamic Boarding School in Banyuwangi Regency. - Suha Salsabila; Nasirudin Al Ahsani (Maddah: Journal of Advanced Da'wah Management Research, 2026)
Leadership style is a behavior applied by a leader to influence others in achieving organizational goals, including within Islamic educational institutions. The kiai's leadership is a determinant factor in maintaining the sustainability and performance of a pesantren amidst changing times. This study aims to: 1) identify and describe the leadership style of Kiai Mahbub Wijaya in maintaining the existence of Nuhuudliyyah Islamic Boarding School in Banyuwangi Regency; and 2) describe the existence of the pesantren for the institution, students, and the surrounding community.This study utilizes a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data condensation, data display, and conclusion drawing. The results indicate that Kiai Mahbub Wijaya, as the leader of Nuhuudliyyah Islamic Boarding School, applies a transformational leadership style characterized by a clear vision, humanistic approach, effective communication, and adaptability. His leadership is reflected in decision-making through deliberation, motivating students and staff, building exemplary behavior, and managing emotions wisely. This leadership style has proven effective in maintaining institutional sustainability, improving human resource quality, and strengthening social-religious contributions to the community.